PENGETAHUAN PELAJAR SEKOLAH DASAR TENTANG PUBERTAS DI JAKARTA DAN SEKITARNYA: - Nurfadhilah Nurfadhilah; Rika Sa'diyah; Nurjannah Achmad; Safia Shukri Hilowle (IAKMI South Tangerang Branch, 2022)
Abstract Background: National surveys show that lack of Indonesian adolescents' knowledge regarding puberty, whereas menarche onset at the age of 9 years. Objective: This study aims to identify the puberty knowledge of elementary school students with gender-based analysis. Method: The method used is an online survey and analysis using an independent T-test equipped with item knowledge analysis. The samples taken were 221 elementary school students throughout Indonesia. Result: The knowledge of female students was significantly higher than that of male students. While the One-way ANOVA test shows that the difference in knowledge based on level/class is not significant, however, if first-year students’ data is ignored, it can be seen that the higher the level, the higher the students' knowledge. Conclusion: Knowledge of puberty is important as a fundamental for abstinence as a behavior to prevent adolescent reproductive health problems, including HIV and other Sexually Transmitted Infections. Massive, measurable, and planned interventions need to be carried out on an ongoing basis to be able to increase the knowledge of elementary school students regarding puberty. Keywords: puberty, knowledge, students, elementary school